Prevalence of exclusive breastfeeding and factors associated with faulty feeding in southwest Bihar - Kumar, Vijay; Kumar, Sanjay; Nitin Gandhi, Devdarshan; Kumar, Mani Kant (International Journal of Contemporary Pediatrics, 2021)
Background: Exclusive breastfeeding has been defined by WHO as “When an infant has been given only breast milk from his/her mother or a wet nurse or expressed breast milk during first six month of life and no other liquids/solids except necessary medicine and nutrional supplements in form of drops or syrup”. Aim was to Assess the prevalence and factors associated for faulty feeding on exclusive breast feeding practices of children less than six Months. Methods: An institution-based cross-sectional survey was conducted from May 2020 to October 2020 at Narayan medical college, Jamuhar, Rohtas, South Bihar. All mothers who visited for immunization and/or postnatal care services were considered as the study population. Lactating mothers who had under six-month infants were included. We observe the breastfeeding process for five minutes and record as per the WHO B-R-E-A-S-T feed observation form. The observation was done by asking the mother to put her infant to the breast. Results: In this present study 58.5% study subjects were given exclusive breast feeding, 36.25% study subjects were given exclusive breast feeding only for some period and rest 5.25% had not given exclusive breast feeding since birth. In this study 46% study subjects had bottle feeding habit, whereas rest 54% do not had Bottle feeding habit. Conclusions: The Exclusive Breast Feeding was satisfactory (58.5%). Some basic reason for faulty feeding were mothers’ belief that no milk, insufficient milk, baby is sick, mother is working/studying.